Managerial hedging and portfolio monitoring - Alberto Bisin; Piero Gottardi; Adriano A. Rampini (Center for Economic Studies and ifo Institute (CESifo), 2004)
Incentive compensation induces correlation between the portfolio of managers and the cash flow of the firms they manage. This correlation exposes managers to risk and hence gives them an incentive to hedge against the poor performance of their firms. We study the agency problem between shareholders and a manager when the manager can hedge his incentive compensation using financial markets and shareholders cannot perfectly monitor the manager's portfolio in order to keep him from hedging the risk in his compensation. In particular, shareholders can monitor the manager's portfolio stochastically, and since monitoring is costly governance is imperfect. If managerial hedging is detected, shareholders can seize the payoffs of the manager's trades. We show that at the optimal contract: (i) the manager's portfolio is monitored only when the firm performs poorly, (ii) the more costly monitoring is, the more sensitive is the manager's compensation to firm performance, and (iii) conditional on the firm's performance, the manager's compensation is lower when his portfolio is monitored, even if no hedging is revealed by monitoring.
Keywords: G30; D82; 330; executive compensation; incentives; monitoring; corporate governance; Führungskräfte; Leistungsorientierte Vergütung; Aktienoptionsplan; Hedging; Portfolio-Management; Leistungskontrolle; Agency Theory; Theorie